“An Essay on Thunder and Small Beer”: a Systemic Approach to Thackeray’s Preface to The Kickleburys on the Rhine - Maxime Leroy (Cahiers Victoriens et Edouardiens)
Thackeray’s preface was written in response to an unfavourable review published in The Times. Using systemic triangulation will consist in reading it from three different but complementary angles: its functional, structural and historical aspects. The article will show how the preface is part of a broader peritextual pattern in which Thackeray defines the roles of author and reader both from a literary and an economic perspective.